Upper-tropospheric pollutants observed by MIPAS: geographic and seasonal variations - N. Glatthor; G. P. Stiller; T. von Clarmann; B. Funke; S. Kellmann; A. Linden (Atmospheric Chemistry and Physics)
We present a global climatology of upper-tropospheric hydrogen cyanide (HCN), carbon monoxide (CO), acetylene (C2H2), ethane (C2H6), peroxyacetyl nitrate (PAN), and formic acid (HCOOH) obtained from observations of the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) on board the Environmental Satellite (Envisat) between 2002 and 2012. At northern midlatitudes and high latitudes, the biomass burning tracer HCN, but also CO, PAN, and HCOOH, exhibit maxima during spring and/or summer and minima during winter. On the contrary, maximum northern extratropical C2H2 and C2H6 amounts were measured during winter and spring, and minimum values were measured during summer and fall. In the tropics and subtropics, enhanced amounts of all pollutants were observed during all seasons, especially widespread and up to southern midlatitudes during austral spring. Other characteristic features are eastward transport of anthropogenic C2H6 and of biogenic HCOOH from Central and North America in boreal summer, accumulation of pollutants in the Asian monsoon anticyclone (AMA), and enhanced C2H2 over southeastern Asia in boreal winter. Clear indication of biogenic release of HCOOH was also found above tropical South America and Africa. A global correlation analysis of the other pollutants with HCN corroborates common release by biomass burning as a source of the widespread southern hemispheric pollution during austral spring. Furthermore, high correlation with HCN points to biomass burning as a major source of tropical and subtropical C2H2 and PAN during most of the year. In the northern extratropics, there are generally low correlations with HCN during spring and early summer, indicating the influence of anthropogenic and biogenic sources. However, in August, there are stronger correlations above Siberia and boreal North America, which points to common release by boreal fires. This is confirmed by the respective enhancement ratios (ERs). The ERs measured above northeastern Africa fit well to the emission ratios of the dominant local fire type (savanna burning) for C2H2, while those for CO, C2H6, and HCOOH rather indicate tropical forest fires or additional anthropogenic or biogenic sources. The southern hemispheric ΔC2H6/ΔHCN<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="74pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="ef4c16a1fc51e58a967532eec31bd8b5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1175-2025-ie00001.svg" width="74pt" height="14pt" src="acp-25-1175-2025-ie00001.png"/></svg:svg> ERs obtained during August to October are in good agreement with the emission ratio for savanna fires. The same applies for ΔC2H2/ΔHCN<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="74pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="128f7d9050ce8e575a7c502ae96dfcc1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1175-2025-ie00002.svg" width="74pt" height="14pt" src="acp-25-1175-2025-ie00002.png"/></svg:svg> in August and for ΔHCN/ΔCO<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="64pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="43d71f300f80f945ad26d496f659c1b5"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1175-2025-ie00003.svg" width="64pt" height="14pt" src="acp-25-1175-2025-ie00003.png"/></svg:svg> and ΔHCOOH/ΔHCN<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="89pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="f0464ba7c2e02ff6b5c89b131002b1db"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-1175-2025-ie00004.svg" width="89pt" height="14pt" src="acp-25-1175-2025-ie00004.png"/></svg:svg> in October.